2022
DOI: 10.1007/s10566-022-09725-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Youth Perceptions of Being Known and Loved and Positive Youth Development: Cross-National Findings from Rwanda and El Salvador

Abstract: Background Dynamic, relational developmental systems-based models of development emphasize that developmentally-nurturant youth-adult relationships elicit in youth perceptions of being known and loved. Although such perceptions are foundations of positive youth development (PYD), such measures do not exist. Objective We sought to create a theoretically-predicated measure of youth perceptions of being known and loved by capitalizing on data sets in two countries (Rwanda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Social relationships are key components of the "Big Three," and similarly, they are key components in the development of youth spirituality. As Tirrell et al (2023) demonstrated, feeling known and loved (KL) by adults is an important developmental asset of youth programs because these feelings are markers of the presence of developmentally nurturant relationships existing in a program, and such relationships are foundations of many developmental outcomes that are important goals in these settings (e.g., transcendence, contribution; e.g., Cantor et al, 2021). These developmentally nurturant relationships also impact how youth grow in their personal spirituality because relational variables have been linked to positive spiritual and psychological development (Augustyn et al, 2017).…”
Section: Spirituality Within the Big Three Features Of Pyd Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social relationships are key components of the "Big Three," and similarly, they are key components in the development of youth spirituality. As Tirrell et al (2023) demonstrated, feeling known and loved (KL) by adults is an important developmental asset of youth programs because these feelings are markers of the presence of developmentally nurturant relationships existing in a program, and such relationships are foundations of many developmental outcomes that are important goals in these settings (e.g., transcendence, contribution; e.g., Cantor et al, 2021). These developmentally nurturant relationships also impact how youth grow in their personal spirituality because relational variables have been linked to positive spiritual and psychological development (Augustyn et al, 2017).…”
Section: Spirituality Within the Big Three Features Of Pyd Programsmentioning
confidence: 99%
“…Next, to assess the convergent validity of a new scale developed to measure youth perceptions of being KL within the context of the youth development program, Tirrell et al (2023) established cross-national invariance of the measurement model between samples of youth from El Salvador and Rwanda and, in doing so, found significant and moderate correlations between the KL scale and the established transcendence subscale of the MDAS ( r s = .45 and .59 for the El Salvador and Rwanda samples, respectively). The finding, that youth spirituality correlates with overall feelings of being KL, is an important point for FBOs to consider in program design because increasing feelings of being KL within the program might also enhance youth spirituality.…”
Section: Case Study: the Compassion International Study Of Pydmentioning
confidence: 99%
See 1 more Smart Citation